Enhancing Tomato Yield in Hot Climates through QTL for Qatar’s Food Security - Gerry Aplang Jana (3155799) (2025)
High-temperature stress is a major limiting factor affecting year-round tomato production in Qatar. In line with the Qatar National Vision 2030, which prioritizes self-sufficiency in domestic agricultural production, the development of elite tomato varieties adapted to local environmental conditions is essential. To explore genetic bases for heat tolerance, 329 transcontinental tomato genotypes were evaluated at the Ministry of Municipality (MM) greenhouses. Initial phenotypic screening identified 71 hybrid and pure-line genotypes for further evaluation. Significant differences were observed among these genotypes for traits such as fruit size, fruit weight, fruit firmness, number of locules, fruit set, total soluble solids (TSS), and fruit yield. To investigate the genetic basis of this variation, the selected subset was genotyped using 104 SNP markers previously associated with heat tolerance in genome-wide association studies (GWAS). Nineteen QTL-linked SNP markers reliably identified heat-tolerant genotypes with superior fruit yield, fruit set, and TSS. Notably, eighteen of these markers were mapped within gene bodies. Based on combined phenotypic and genotypic analyses, an elite set of five genotypes was identified for potential release under heat-stress conditions in Qatar. This study provides a foundation for marker-assisted breeding to advance tomato improvement in hot-arid environments of Qatar. Other Information Conference information: 18th Edition of the Qatar University Life Sciences Symposium Bio-Environment: Advances and Innovations. (26 - 27 Nov 2025, Qatar University, Doha - Qatar) License: https://creativecommons.org/licenses/by/4.0/ See the conference information on the organizer's website: https://www.qu.edu.qa/en-us/conference/QULSS2025/Pages/default.aspx